Reusing treated effluent in concrete technology - Ooi, Soon Lee; Salim, Mohd. Razman; Ismail, Mohammad; Ali, Md. Imtiaj (Penerbit UTM Press, 2001)
In this paper, the feasibility of using treated effluent for concrete mixing was studied. Treated effluent from sewage treatment plants in Malaysia is currently being wasted through direct discharge into waterways. With proper water quality control, this treated effluent can also be considered as a potential water resource for specific applications. Two tests were carried out namely compressive strength test and setting time to determine the feasibility of using treated effluent for concrete mixing. The results were compared against the tests conducted on control specimens which used potable water. The results showed that treated effluent increases the compressive strength and setting time when compared with potable water.